Treatment for Scoliosis Using Pneumatic Control System - Mohana Lakshmi, A; Jofiny, Sharon; Sindhuja, P; V.Jason Jebasingh, G; Suresh Chander Kapali, B (International Journal of Engineering and Technology, 2018)
Now a day’s curvature of spine is a common problem from babies to adults. In this paper, a wearable brace is used to provide patient to overcome from scoliosis by wearing braces with controlled pressure. Scoliosis is one of the spine diseases, the spine will be in S shape or C shape, in some degree of curve. But mostly occurs in Juvenile stage (3-10 years) and also women face this problem. It can be cured by a proper treatment by wearing a brace. The pressure control system is microcontroller. Bracing is a common non-surgical treatment for scoliosis, more often the patient wear their braces to the prescribed tightness. It works by applying corrective pressure on the outer side of curve and cutting out respective areas of relief to inner side of curve ,so the spine can migrate in that direction. The pressure control device was developed to understand brace wear time and regulate a target pressure range. The pressured data is transmitted to the central processing station. The effectiveness of our system is to monitor the development of posture of spine by wearing braces with controlled pressure.